Transgenic Expression of Human C-Type Lectin Protein CLEC18A Reduces Dengue Virus Type 2 Infectivity in Aedes aegypti - Cheng, Lie; Liu, Wei-Liang; Tsou, Yun-Ting; Li, Jian-Chiuan; Chien, Chia-Hao; Su, Matthew P.; Liu, Kun-Lin; Huang, Ya-Lang; Wu, Shih-Cheng; Tsai, Jih-Jin; Hsieh, Shie-Liang; Chen, Chun-Hong (Frontiers in Immunology, 2021)
The C-type lectins, one family of lectins featuring carbohydrate binding domains which participate in a variety of bioprocesses in both humans and mosquitoes, including immune response, are known to target DENV. A human C-type lectin protein CLEC18A in particular shows extensive glycan binding abilities and correlates with type-I interferon expression, making CLEC18A a potential player in innate immune responses to DENV infection; this potential may provide additional regulatory point in improving mosquito immunity. Here, we established for the first time a transgenic Aedes aegypti line that expresses human CLEC18A. This expression enhanced the Toll immune pathway responses to DENV infection. Furthermore, viral genome and virus titers were reduced by 70% in the midgut of transgenic mosquitoes. We found significant changes in the composition of the midgut microbiome in CLEC18A expressing mosquitoes, which may result from the Toll pathway enhancement and contribute to DENV inhibition. Transgenic mosquito lines offer a compelling option for studying DENV pathogenesis, and our analyses indicate that modifying the mosquito immune system via expression of a human immune gene can significantly reduce DENV infection.